Legal Politics in the Indonesian Presidential System: How to Leverage Potential of Asset Forfeiture Bill for Corruption Eradication? - Fernando Holqi, Fikri Gali (Asia Social Issues, 2025)
This study examines the potential for the ratification of the Asset Forfeiture Bill in Indonesia, particularly by the Parliament for the 2024-2029 period, and its role in the eradication of corruption. The analysis includes the legal politics of law formation in Indonesia, the political party coalition composition in the 2024-2029 Parliament (MAP). and the potential for the promulgation of the Asset Forfeiture Bill. This research employs a qualitative method using juridical normative approaches, with legal and conceptual analyses. Primary legal materials include laws, while secondary legal materials encompass rulings, journals, and books. The data are analyzed through the lens of Legal Politics theory. The study indicate that the House of Representatives and the President in Indonesia can initiate the Bill. Furthermore, the President can also make a Perppu. However, any presidential initiative requires approval from the DPR. The position of the DPR is crucial, reflecting the dominant role of the legislative institution. The composition of the KIM coalition in Parliament increases the likelihood of passing the Asset Forfeiture Bill. However, passing the Asset Forfeiture Bill could potentially criminalize and delegitimize the law, so it is necessary to emphasize enforcing the LHKPN law.This study examines the potential for the ratification of the Asset Forfeiture Bill in Indonesia, particularly by the Parliament for the 2024-2029 period, and its role in the eradication of corruption. The analysis includes the legal politics of law formation in Indonesia, the political party coalition composition in the 2024-2029 Parliament (MAP). and the potential for the promulgation of the Asset Forfeiture Bill. This research employs a qualitative method using juridical normative approaches, with legal and conceptual analyses. Primary legal materials include laws, while secondary legal materials encompass rulings, journals, and books. The data are analyzed through the lens of Legal Politics theory. The study indicate that the House of Representatives and the President in Indonesia can initiate the Bill. Furthermore, the President can also make a Perppu. However, any presidential initiative requires approval from the DPR. The position of the DPR is crucial, reflecting the dominant role of the legislative institution. The composition of the KIM coalition in Parliament increases the likelihood of passing the Asset Forfeiture Bill. However, passing the Asset Forfeiture Bill could potentially criminalize and delegitimize the law, so it is necessary to emphasize enforcing the LHKPN law.